Investigation of energy and exergy performance of A 3 KW steam power plant - Muhammad Rusydi Hassim, 1995-, author; Aminuddin Saat, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Sains (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2018